The promoter T-413A variant and elevated enzyme levels of heme oxygenase-1 associated with an increased risk of polycystic ovarian syndrome - Wang, Qiuyi; Liang, Jiagui; Liu, Qingqing; Liu, Hongwei; Bai, Huai; Huang, Wei; Fan, Ping (Frontiers in Endocrinology, 2025)
BackgroundOxidative stress and metabolic disorders significantly contribute to the development of polycystic ovarian syndrome (PCOS). Heme oxygenase-1 (HMOX1) plays a key role in the degradation of heme and the regulation of oxidative stress, ferroptosis, and glycolipid metabolism. This study explored the relationship between HMOX1 promoter T-413A single nucleotide polymorphism (SNP, rs2071746), (GT)n dinucleotide repeat variant (rs3074372), plasma HMOX1 levels, and the risk of PCOS in Chinese women.MethodsThis case-control study included 1092 women diagnosed with PCOS and 805 controls. The (GT)n and rs2071746 polymorphisms were identified using polymerase chain reaction amplification, followed by capillary electrophoresis or restriction fragment length polymorphism. HMOX1 levels and clinical, metabolic, hormonal, and oxidative stress indices were analyzed.ResultsThe HOMX1 rs2071746T/A SNP was associated with an increased risk of PCOS based on genotype, recessive, dominant, and allele genetic models (P < 0.05). After adjusting for age, body mass index, and recruitment year of participants, the dominant model (odds ratio [OR] = 1.272, 95% confidence interval [CI]: 1.013–1.597, P = 0.039) and the TT genotype (OR = 1.395, 95% CI: 1.033–1.883, P = 0.030, with the AA genotype as the reference) remained a significant predictor of PCOS in the logistic regression models. No significant differences were observed in the (GT)n polymorphism of HMOX1 based on different genetic models. However, the TT/SS combined genotype of HMOX1 rs2071746T/A and (GT)n polymorphisms was associated with an increased risk of PCOS (OR = 1.442, 95% CI: 1.021–2.035, P = 0.037). Furthermore, elevated HMOX1 levels were related to a slight but significant increase in the risk of PCOS, and the rs2071746T/A and (GT)n genetic variants significantly affected obesity, oxidative stress, endocrine abnormalities, and metabolic disorders.ConclusionHMOX1 rs2071746T/A variant and elevated plasma HMOX1 levels are associated with an increased risk of PCOS.